From the role of cooperative law for development to sustainable development and cooperative law - Henrÿ, Hagen (Cooperativismo & Desarrollo, 2025)
This article explores the relationship between cooperative law, development, and sustainable development. It argues that cooperative law is not just a tool but a principle that aligns with the International Cooperative Alliance’s cooperative principles. It delves into the evolution of the concept of “development,” which has shifted from economic growth to a multidimensional process, incorporating social, political, and environmental dimensions. The article traces this transformation, highlighting the significant role law plays in shaping development. It further argues that cooperative law, rooted in democratic principles, can contribute to sustainable development by promoting social justice, diversity, and equality. The text also examines the emergence of sustainable development as a legal principle in international law, emphasizing the human right to sustainable development. The contribution suggests that cooperative law’s unique structure allows it to regenerate social justice, especially in intercultural and global contexts. It concludes by asserting that cooperative law is essential for achieving a just, sustainable future.